1993
DOI: 10.1080/00288233.1993.10417760
|View full text |Cite
|
Sign up to set email alerts
|

Carcass fatness in lambs grazing various forages at different rates of liveweight gain

Abstract: In three experiments, Dorset, Suffolk cross, or Coopworth lambs weighing c. 30 kg in January were offered a range of forages including high-endophyte Nui ryegrass-dominant pasture, white clover-dominant pasture, Moata or Concord ryegrasses, lucerne, rape, or chicory. Herbage allowances were adjusted to achieve target liveweight gains of 300, 200, or 120 g/day and lambs slaughtered at c. 43 kg liveweight from March to May. In Experiment 1, medium and low rates of liveweight gain were compared on both ryegrassdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…There were also no significant between-forage differences in depth of LD muscle or subcutaneous fat at finish. This is in agreement with previous reports that forage type has little effect on carcass composition (Nicol & Mclean 1970;Scales 1993), although Purchas & Keogh (1984) reported leaner carcasses of lambs grazed on Lotus pedunculatus than when grazed on white clover. Carcass weights and killing out percentages for all forages were lower than those obtained by Karnezos et al (1994).…”
Section: Finishing Lambssupporting
confidence: 93%
“…There were also no significant between-forage differences in depth of LD muscle or subcutaneous fat at finish. This is in agreement with previous reports that forage type has little effect on carcass composition (Nicol & Mclean 1970;Scales 1993), although Purchas & Keogh (1984) reported leaner carcasses of lambs grazed on Lotus pedunculatus than when grazed on white clover. Carcass weights and killing out percentages for all forages were lower than those obtained by Karnezos et al (1994).…”
Section: Finishing Lambssupporting
confidence: 93%
“…This may indicate a higher gut fill in the brassica fed lambs, consistent with the reduced ME of this forage. There is evidence that lambs fed on brassicas will be fatter than those finished on grass (Scales, 1993), a finding supported by the work of Hopkins et al (1995a). In that latter study, again without replication of the treatments, brassica fed lambs had a higher DP than lambs finished on pasture.…”
Section: Tablementioning
confidence: 72%
“…Butler-Hogg and [ohnsson (1986), however, suggested that a higher growth rate could lead to leaner carcasses. The apparent contradiction may arise because the composition of the food changes the effect that growth rate has on carcass composition (Scales, 1993). Lewis et al (2004) showed that lower food protein content decreased growth rate and increased fatness.…”
Section: Carcass Compositionmentioning
confidence: 99%